Comprehensive league table of cost-utility ratios: A systematic review of cost-effectiveness evidence for health policy decisions in India - Shah, Komal; Singh, Malkeet; Kotwani, Priya; Tyagi, Kirti; Pandya, Apurvakumar; Saha, Somen; Saxena, Deepak; Rajshekar, Kavitha (Frontiers in Public Health, 2022)
Background and objectives: Though a relatively recent concept for developing countries, the developed world has been using League Tables as a policy guiding tool for a comprehensive assessment of health expenditures; Country specific “League tables” can be a very useful tool for national healthcare planning and budgeting. Presented herewith is a comprehensive league table of Cost per Quality Adjusted Life Years (QALY) or Disability Adjusted Life Years (DALY) ratios derived from Health Technology Assessment (HTA) or economic evaluation studies reported from India through a systematic review. Methods: Economic evaluations and HTAs published from January 2003 to October 2019 were searched from various databases. We included only the studies reporting common outcomes (QALY/DALY) and methodology to increase the generalizability of league table findings. In order to opt for a uniform criterion, a reference case approach developed by Health Technology Assessment in India (HTAIn) was used for the reporting of the incremental cost-effectiveness ratio. However, as, the majority of the articles expressed the outcome as DALY both (QALY & DALY) were used as outcome indicators for this review. Results: After the initial screening of 9,823 articles, 79 articles meeting the inclusion criteria were selected for League table preparation. The spectrum of intervention was dominated by innovations for infectious diseases (33%), closely followed by maternal and child health (29%), and non-communicable diseases (20%). The remaining 18% of the interventions were on other groups of health issues such as injuries, snake bites, and epilepsy. The majority of the interventions (70%) reported DALY as an outcome indicator and the rest (30%) reported QALY. Outcome and cost were discounted at the rate of 3% by 73% of the studies, at 5% by 4% of the studies, whereas 23% of the studies did not discount it. Budget impact and sensitivity analysis was reported by 18% and 73% of the studies respectively. Interpretation and conclusions: The present review offers a reasonably coherent league table that reflects ICER values of a range of health conditions in India. It presents an update to decision-makers for making decisions pertaining to health resource allocation.